Development and Evaluation of Self-Propelled Cono Weeder for Rice Cultivation in Vertisol - Ningthoujam, Bishorjit; Shrivastava, Atul Kumar (Indian Journal of Hill Farming, 2019)
Weeding is one of the important agricultural operation. 30 to 60 per cent of crop yield is affected due to improper weeding. Intercultural/weeding operation in paddy crop is very important operation where the worker in bending position used to uproot the weeds that might affect their health therefore it is quite necessary to have suitable agricultural implements which farmers can use and also allow them to use for custom hiring. A selfpropelled cono weeder was developed and tested ergonomically and mechanically. The frame of the developed self-propelled cono weeder was fabricated from hollow square pipe of 25 x 25 mm having a thickness of 2 mm. The supporting drive wheel of weeder (600 mm diameter) was fabricated from mild steel rod of 8 mm. A 1kW (1.3HP) petrol engine is used as its power source. The travel speed, weeding efficiency, field capacity and fuel consumption od developed powered cono weeder were found to be 2.28 km/h, 68.77 %, 0.0323 ha/h and 6.77 l/ha respectively. The peak heart rate, oxygen consumption rate and energy expenditure rate for operating self-propelled cono weeder by women workers were found to be 11.34 beats/min, 0.668 l/min and 13.94 KJ/min respectively.